The impact of obesity on the risk of musculoskeletal injuries in children – a review of the literature - Matuszewska, Julia; Lambach, Jakub; Miazga, Dominika; Woźnica, Weronika; Kutnik, Kacper; Maziarczyk, Alicja; Dąbrowska, Julia; Białogłowski, Michał; Mazurek, Katarzyna (Quality in Sport, 2025)
Introduction Childhood obesity is an increasing public health issue that leads not only to metabolic disorders but also to significant orthopedic complications. Excess body weight affects the developing musculoskeletal system, alters biomechanics, limits mobility, and increases the risk of injuries, particularly in the lower limbs. Aim The aim of this review is to summarize current evidence on the relationship between obesity in school-aged children and the risk of musculoskeletal injuries, with a focus on lower limb fractures and the biomechanical mechanisms that heighten injury susceptibility. Material and Methods This narrative review includes epidemiological studies, cohort analyses, clinical reports, and biomechanical research examining fracture patterns, treatment outcomes, gait alterations, and loading forces in obese pediatric patients. Results The available evidence shows that obese children are more likely to experience injuries of the lower extremities, and these injuries tend to be more severe and complex. Increased kinetic energy during falls, altered biomechanics with abnormal load distribution, and reduced balance and neuromuscular control all contribute to this higher risk. Treatment challenges, such as difficulties with casting or surgical procedures, are also more common in this group. Conclusions The heightened risk of musculoskeletal injuries among obese children underscores the need for targeted prevention, promotion of healthy lifestyles, and adjustments in clinical care. A multidisciplinary approach involving pediatricians, orthopedists, physiotherapists, and nutrition specialists is essential to reduce injury risk and improve overall health outcomes.